Torakochirurgia Postintubation rupture of the trachea in thoracic surgery - Ciszewski, Paweł; Skrzypczak, Mariusz; Chorąży, Zofia; Tyczka, Joanna; Nadolski, Jacek; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Postintubation tracheal rupture is a very rare but serious and life-threatening intraoperative complication. So far there are no uniform therapeutic algorithms for treatment of patients with such iatrogenic ruptures. Aim: This study presents two case reports of tracheal lesion caused by intubation for thoracic surgery and the results of its treatment. Material and methods: Over a period of 10 years (1995-2005) we conducted about 5000 double lumen tube intubations in our institution. Postintubation rupture of the trachea occurred in three patients and in all cases was localized in the posterior part of the trachea. Results: In the presented cases, both conservative and surgical treatment were applied with good results. Conclusion: In our opinion intraoperative lesion of the trachea of more than 1 cm in length requires surgical repair. In case of injury diagnosed after thoracotomy and in all other cases when direct access to the trachea is possible, early surgical repair is also recommended regardless of the size of the rupture.